(untitled) (Journal of Dhaka Medical College, 2015)
Acute promyelocytic leukemia (APL)-FAB-AML-M3 is now the most curable subtype of acute myeloblastic leukemia. The incidence of acute leukemia in pregnancy is rare. The occurrence of acute promyelocytic leukemia in pregnancy is also a very rare but management is very critical as APL is associated with life threatening hemorrhagic diathesis. Acute promyelocytic leukemia in pregnancy has not been reported in Bangladesh. Here we report a case of APL with DIC diagnosed during pregnancy. Clinical data and therapeutic approaches are presented. Her response to treatment was excellent resulted in a live birth and complete remission of her leukemia. J Dhaka Medical College, Vol. 23, No.2, October, 2014, Page 262-265